Невидимая смерть: [роман] / Евгений Федоровский - Федоровский Евгений Петрович (Военные приключения, 2016)
Экземпляры: ф.18 (20201027) / Инвентарный номер: 3599 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ф 33 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44